INKORPORASI OLEAT DAN EKSTRAK ANTOSIANIN PADA FILM GELATIN SEBAGAI INDIKATOR pH UNTUK KEMASAN PINTAR - Azis Boing Sitanggang; Muhammad Fakhrian Irsali; Saroat Rawdkeun (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
This study was aimed to develop and investigate the characteristics of the intelligent films made from gelatin with oleic acid (OA) and anthocyanin extract incorporation. Anthocyanin was extracted from red cabbage (RC), sweet potato (SP), black bean coat seed (BB), and purple rice (CR), and then tested for pH sensitivity. Anthocyanin from SP was selected as it showed the highest pH sensitivity. Gelatin film was incorporated with 20% of anthocyanin extract and 50% OA. The films with OA and anthocyanin extracts incorporation was selected for application as the color changes can be observed clearly at pH 2-11. Red color was present on the film added with anthocyanin extract from SP. OA incorporation significantly decreased the elongation of the film, while it was on the contrary for anthocyanin extract incorporation. Both OA and anthocyanin extracts incorporation decreased thickness, moisture content, and tensile strength of the film significantly (P<0.05). Additionally, there was a reduction trend of water vapor permeability for gelatin film incorporated with OA and anthocyanin. However, this reduction was insignificantly different with the control (P>0.05). The incorporation of OA provided wavier surfaces while anthocyanin extract incorporation enhanced the compactness and smoothness of the films, and provided smoother surfaces of the film. A higher enthalpy was needed for melting the film with anthocyanin extract.